A giant barnacle (Crustacea, Cirripedia, Thoracica) from the Upper Cretaceous (Maastrichtian) of Canada revisited. Issue 3 (June 2022) - Gale, Andy
Abstract: The cirripede Calantica ? saskatchewanensis Russell, 1967, from the Maastrichtian Bearpaw Formation of Saskatchewan (Canada), is redescribed on the basis of new material and transferred to the genus Pachyscalpellum Buckeridge, 1991. This considerably extends the known range of the genus from the eastern Tethys (Australasia, Tunisia) to the northern part of the Western Interior Seaway of North America. Species of the genus achieved an exceptionally large size for stalked barnacles, with a projected possible height (capitulum and peduncle) of 150–200 mm.